Manner of Interaction of Heterogeneous Claudin Species within and between Tight Junction Strands - Furuse, Mikio (The Rockefeller University Press, 1999)
In tight junctions (TJs), TJ strands are associated laterally with those of adjacent cells to form paired strands to eliminate the extracellular space. Claudin-1 and -2, integral membrane proteins of TJs, reconstitute paired TJ strands when transfected into L fibroblasts. Claudins comprise a multigene family and more than two distinct claudins are coexpressed in single cells, raising the questions of whether heterogeneous claudins form heteromeric TJ strands and whether claudins interact between each of the paired strands in a heterophilic manner. To answer these questions, we cotransfected two of claudin-1, -2, and -3 into L cells, and detected their coconcentration at cell–cell borders as elaborate networks. Immunoreplica EM confirmed that distinct claudins were coincorporated into individual TJ strands. Next, two L transfectants singly expressing claudin-1, -2, or -3 were cocultured and we found that claudin-3 strands laterally associated with claudin-1 and -2 strands to form paired strands, whereas claudin-1 strands did not interact with claudin-2 strands. We concluded that distinct species of claudins can interact within and between TJ strands, except in some combinations. This mode of assembly of claudins could increase the diversity of the structure and functions of TJ strands.